Identification of Urban Farming in The Green Kampong Yogyakarta - Pasha, Riza Fadholi; Widyaningsih, Sheily; Rijanta, R. (Jurnal Tata Kota dan Daerah, 2014)
The most visible of the city development defined by the physical aspect such as the growth of the built-up area. The continuity of built-up area’s growth will decrease the carrying capacity of the region. In term of urban planning is worth considering the provision of green open space which is has the function of environmental protection. One of urban green open space named agriculture. Farming the urban area now is popular with Urban Farming. The benefits of urban farming are (1) increasing the income level of city; (2) building up the job opportunity; and (3) optimizing the urban space. This research takes place in Yogyakarta to inventory and to describe the urgency of urban farming. This research uses qualitative descriptive method by analyzing secondary data and surveying in sample spots of Urban Farming been done. Sample spots are decided by purposive sampling in kampong hijau (the green kampong) Yogyakarta. The result is in green kampong are mostly planted by consumption plants and ornamental plants. It is being urgent alternative to be done in limited area where women and people are not only competitive again for working but also help them fulfilling the daily consumption on farming products and environmental preservation.Keywords: Urban Farming, Green Kampong, Yogyakarta, Identification, Urgency